MODEL ANTECEDEN LOYALITAS KONSUMEN ( STUDI DI RUMAH SAKIT RSUD KOTA SEMARANG) - Wismantoro, Yohan (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2011)
The research examine satisfaction dan loyalty in RSUD Semarang. Data analysis techniques used the structural equation model (SEM) with 115 samples of datas. From the analysis it can be concluded that the dimensions of physician services, nursing services, inpatient room comfort and the environment, long waiting time, non-medical staff services and payment service contribute to the quality of service at the Semarang City RSUD. Service quality significantly influence patient satisfaction the semarang City RSUD. Quality of service does not significantly influence patient loyalty the Semarang City RSUD. Satisfaction significantly influence to patient loyalty the Semarang City RSUDKeywords: quality of service, patient satisfaction, loyalty